Do executive functions explain older adults' health-related quality of life beyond event-based prospective memory?. Issue 2 (4th March 2023) - Laera, G.; Joly-Burra, E.; Zuber, S.; Ballhausen, N.; Künzi, M.; Ihle, A.; da Silva Coelho, C.; Haas, M.; Mikneviciute, G.; Tinello, D.; Kliegel, M.; Hering, A.
ABSTRACT: Previous work has shown that event-based prospective memory (EBPM) predicted health-related quality of life (HrQoL). In the present study, we aimed to examine whether the relationship between EBPM and HrQoL extended to life satisfaction, and whether it persisted after controlling for other cognitive functions related to EBPM, namely executive functions and retrospective memory. We tested two models using structural equation modeling with latent variables in a sample of older adults. In the first model, we assessed whether EBPM predicted life satisfaction and HrQoL; in the second model, we controlled for retrospective memory and executive functions. The first model indicated that EBPM was related to HrQoL. However, in the second model, this relationship was eliminated by executive functions; life satisfaction was not related to any of the cognitive variables. Findings corroborated the link between HrQoL and EBPM, suggesting that such relationship stems from executive functions rather than retrospective memory.